Pengembangan LKPD Berbasis PBL Gelombang Bunyi dan Cahaya untuk Meningkatkan Keaktifan dan Kreativitas Kelas V - Zulfi Rokhaniawati; Ikhlasul Ardi Nugroho (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The study aims to: 1) determine the feasibility of PBL-based LKPD on sound and light wave materials to increase the activeness and creativity of class V students, 2) determine the practicality of PBL-based LKPD on sound and light wave materials to increase the activeness and creativity of class V students, and 3) examine the effectiveness of PBL-based LKPD on sound and light wave materials to increase the activeness and creativity of class V students. This development research was conducted in Karangmojo District, Gunungkidul Regency, Special Region of Yogyakarta, in reference to the 5-step ADDIE model developed by Branch. The trial consisted of three steps: a one-on-one trial with three students, a small-group trial with nine students, and a field trial with 22 students. After the trial stage, the implementation stage was continued using quasi-experimental methods with a pretest–posttest control group design. The subjects in the control class consisted of 23 students, and the subjects in the experimental class also comprised 23 students. Data collection techniques through interviews, observations, questionnaires, scales and tests. Data analysis techniques used quantitative and qualitative data analysis. The results of the study show that: 1) PBL-based LKPD on sound and light wave materials has met the eligibility criteria based on the validation of material experts and media experts with the criterion of "very feasible"; 2) PBL-based LKPD on sound and light wave materials has met the practicality criteria based on the results of the teacher and student response questionnaire with the criterion of "very practical"; and 3) PBL-based LKPD on sound and light wave materials was declared "effective" to increase the activeness and creativity of class V students.